Isolation, speciation and antifungal susceptibility patterns of candida isolated from cases of chronic balanoposthitis - Lakshmi, N.; Hemalatha, N. V.; Krishna, P. Bala Murali (International Journal of Research in Medical Sciences, 2017)
Background:Balanoposthitis is a common condition affecting 11% of male genitourinary clinic attendees and it can be a recurrent or persistent condition. Various predisposing factors like diabetes mellitus, sexual intercourse and usage of oral antibiotics can cause chronic balanoposthitis. The Objective of the study was to isolation and speciation of candida and their antifungal susceptibility patterns from the cases of chronic balanoposthitis. Methods: The study group comprised of swabs collected from 62 male patients with chronic balanoposthitis attending sexually transmitted diseases (STD) outpatient department (OPD), King George Hospital (KGH), Visakhapatnam. Standard mycological tests for the candida isolation, speciation and antifungal susceptibility were done. Results: Out of 62 samples, (85%) were culture positive for candida. The most common species isolated was C. parapsilosis (37.7%), followed by C. glabrata (28.3%), C. albicans (15.09%), C. dubliniensis (9.4%), C. krusei (7.5%) and C. tropicalis (1.88%). Most of the candida species showed sensitivity to amphotericin B, Nystatin, clotrimazole and ketoconazole. A relative resistance to fluconazole and itraconazole was observed. Conclusions: Chronic balanoposthitis is the most common infection in men attending STD, OPD. In the present study, diabetes is main predisposing factor than sexual intercourse and candida non albicans predominated over C. albicans. Resistance of candida species to azoles is on rise. This establishes the importance of determination of antifungal susceptibility patterns to prevent the emergence of drug resistance, prior to initiation of therapy.